Sustainable Tourism development and its contribution in facing unemployment phenomenon - حمد سعد ابراهيم (Journal of Economics and Administrative Sciences, 2013)
Tourism is a human phenomenon and economic and social activity. It represents an effective forces in the life of the individuals and state alike. As any other economic and human activity has appositive and negative results. So there is a necessary to planning and activate this sector to get the most possible advantage. Tourism has special importance out of its effect on the structure and performance of national economy. It can be regarded a dynamic activity with mutual effect include all the economic activities within and out the state. Tourism is affected and affect the production con summing , joineries , communication , ports ,hotel , restaurants ,internal and external trade…etc. Moreover, spreading tourist projects to different sites will develop these sites and raising standards of living in theses sites, creating jobs in these poor isolated. Sites, as well as to other activities in these sites then achieving balance and supporting economy in general.